b - 9; 9 (b, 2009)
critical articles on literary notes of Jibanananda Das, 1899-1954, 20th century Bengali poet; includes text of notes and biographical information.
In Bengali; includes English.
Keywords: Das, Jibanananda, -- 1899-1954, -- Criticism and interpretation; Das, Jibanananda, -- 1899-1954, -- Diaries; Poets, Bengali -- 20th century -- Biography; Bengali literature